Corrigir e ajustar: as propostas para a educação nos Arquivos Brasileiros de Higiene Mental (1925-1947) - Carraro, Mariana (2022)
The mental hygiene movement was characterized by the prevention of mental diseases by means of correction and treatment of human psychic and social “maladjustments”. In Brazil, it had the Brazilian League of Mental Hygiene (LBHM) as the protagonist, founded in 1923 in Rio de Janeiro. In its magazine Brazilian Archives of Mental Hygiene (ABHM), the League developed its ideas and plans of action regarding the main social problems of the period, seeking to build a new Brazil. This work follows the perspective of dialectical historical materialism, and adopts bibliographic and documental research and bibliometric and content analysis as methodological procedures. Thus, a broad panorama of the LBHM and the ABHM was drawn, especially regarding the articles that address the theme of education, which make up a significant part of the documentary corpus studied. The objective of the research was to analyze the conceptions of education expressed in the ABHM, between the years of 1925 and 1947, and its role in the project of nation designed by the institution. Content indicators were established for articles referring to school and education published in the ABHM, according to the main subjects addressed by them: Psychology, Special Education, Education and School, Euphrenia and Mental Hygiene and Psychiatry and Psychoanalysis. Investigating how the medical-pedagogical vision disseminated in the ABHM was imposed on the main agents of the educational process - the school, the teachers and the family -, the initial hypothesis was confirmed: that the dissemination of the values of mental hygiene defended by the Brazilian League of Mental Hygiene should start from childhood in the family and at school, in order to “shape” these individuals for their social adjustment according to the concept of “normality” developed by the institution. According to the ABHM, each individual should occupy a specific place in society, and this place was established according to their “capacities”, considered to be mostly biological for most of the authors who wrote in the magazine, equipped with a scientific discourse that intended to be neutral and apolitical.